2020
DOI: 10.3389/fgene.2020.00547
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Expression and Its Clinical Significance of the Secreted Phosphoprotein 1 in Lung Adenocarcinoma

Abstract: Objective: To explore the expression of secreted phosphoprotein 1 (SPP1) in lung adenocarcinoma (LUAD), and evaluate its relationship with clinicopathological characteristics and prognosis of LUAD, and analyze the advantages of SPP1 as a potential prognostic marker in LUAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…More evidence shows that SPP1 was overexpressed in various types of cancers and contributes to the occurrence and development of tumors, including colorectal cancer, cervical cancer, gastric cancer, and so on (27)(28)(29)(30). The result of our finding that SPP1 may be a potential biomarker for lung adenocarcinoma was consistent with several studies (31,32). More reports had illustrated the relationship between the expression level of SPP1 and lung adenocarcinoma.…”
Section: Compared With Normal Tissues Only the Spp1 Expressionsupporting
confidence: 90%
“…More evidence shows that SPP1 was overexpressed in various types of cancers and contributes to the occurrence and development of tumors, including colorectal cancer, cervical cancer, gastric cancer, and so on (27)(28)(29)(30). The result of our finding that SPP1 may be a potential biomarker for lung adenocarcinoma was consistent with several studies (31,32). More reports had illustrated the relationship between the expression level of SPP1 and lung adenocarcinoma.…”
Section: Compared With Normal Tissues Only the Spp1 Expressionsupporting
confidence: 90%
“…Specifically, miR-539-5p emerged with the highest node degrees compared to other nodes in the network. Several studies found that miR-539-5p expression levels associated with a poor prognosis and negatively correlated with hypoxia and the stem index among LUAD patients ( González-Vallinas et al, 2018 ; Guo et al, 2020 ). Yet, further experiments are needed to verify these results given the limited evidence documenting the direct mechanisms of miR-539-5p in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulated SPP1, COL1A1, and COL3A1 in LUAD were positively correlated with each other, while the down-regulated PECAM1, VWF, EDN1, CDH5, and TEK were in LUAD also positively correlated with each other. Guo et al studied the expression and clinical significance of SPP1 in LUAD and found that SPP1 influenced the initiation and progression of LUAD, which was considered as a new target for molecular treatment [ 13 ]. Similarly, we tried to determine the mechanisms of PECAM1 in LUAD.…”
Section: Discussionmentioning
confidence: 99%